KONTRIBUSI AFEKTIF DAN KOGNITIF TERHADAP PSIKOMOTOR DALAM PROJECT BASED LEARNING PRAKTEK REKAYASA BATU DAN BETON MAHASISWA PRODI PENDIDIKAN TEKNIK BANGUNAN TAHUN MASUK 2018 - Lusi Nofianti; Dr. Nurhasan Syah, M.Pd (CIVED, 2019)
Abstract: This study aims to look at the contribution of Project Based Learning methods to affective, cognitive and psychomotor practices of Stone and Concrete Engineering Building Engineering Education Study Program  in 2018. This type of research is quantitative research with a correlational approach. The population in this study were students of Building Engineering Education study program with section code 20181060018 who were taking courses in Stone and Concrete Engineering. The number of students is 17 people. Sampling uses a saturated sampling technique. The variables studied were three variables, namely affective (X1), cognitive (X2), and psychomotor (Y). The procedure in this study consists of three stages, namely the preparation stage, the implementation phase, and the final stage. The data of this study were carried out by participant observation. The instrument used was a performance test along with a skill observation sheet using the results scale. Data were analyzed with the help of SPSS version 17.0 for Windows and Microsoft Excel. The results showed that  there  were influences between psychomotor affective with a large influence of 23.71%, and the influence between psychomotor cognitive was 26.52%, and the influence between affective to psychomotor was 44.7%, which was quitehigh. Keywords: Project-based learning method, Learning Outcomes, Stone and Concrete Engineering